Comparison Of Individual and Collaborative Learning in Offline Teaching - Kenjaeva Fotima; Kenjaeva Zuhra (Zien Journals, 2021)
This article speaks about the comparison of individual and collaborative learning in face-to-face learning using reading and writing tasks to define the motivation and academic achievement of learners. The framework took place during the fall semester using 24 students who study at the Academy of the Ministry of Internal Affairs of the Republic of Uzbekistan. In the study, it is used reading and writing tasks to define the best learning methods with regards to motivation and academic success. It was decided that collaborative learning is more effective with learners in terms of academic success and motivation compared to individual learning. However, individual learning was higher in informative writing than cooperative learning.
Keywords: individual; interaction; cognitive process; critical thinking.